Community perspectives of mathematics and statistics support in higher education: the role of the staff member. (12th January 2018) - Grove, Michael; Croft, Tony; Lawson, Duncan; Petrie, Moira
Abstract: Mathematics support now forms a widely accepted and important part of the provision of higher education institutions within the UK and Ireland to assist students within their learning of mathematics and statistics, particularly as they make the transition to university study. Over the last 15 years it has seen growth as an area of scholarship, and behind this has been the role of those staff members who oversee, develop, deliver and research mathematics support within their institutions. To date, however, there has been little work that explores the roles, opportunities and recognition afforded to such individuals, but this is important if visibility for mathematics support as part of the provision and practice of higher education institutions is to continue to grow and a sustainable community of practitioners is to be established. Here we report on a survey of 51 individuals with responsibility for the day-to-day operation of the mathematics and statistics support provision within their institutions. Findings show that the majority of staff with such responsibility for the delivery of mathematics support within institutions are in permanent roles and that in many instances this forms the sole focus of their employment; there also exists an important and visible role for postgraduates in the delivery of mathematics support. Finally, there is evidence that most staff working in this area feel recognized and well supported with opportunities to develop their roles, engage with professional development and contribute to a national community of practice.